Integrated Optimization of Cyclohexane Production via Benzene Hydrogenation Incorporating Advanced Separation, Extended Distillation, and Heat Exchanger Integration to Enhance Product Purity and Energy Efficiency - Muhammad Trisna Mi'raji Artha; Wildan Aunur Rofiq; Muhammad Ihsan Aqilah; Ru'ullah Khalif Umar; Nayyara Alifah Ardelia (Journal of Chemical Engineering Research Progress, 2025)
Cyclohexane is an essential intermediate in the production of nylon-based polymers, yet its industrial synthesis via benzene hydrogenation and subsequent purification remains challenged by thermodynamic limitations and the narrow boiling-point gap between benzene and cyclohexane. This study presents an integrated process optimization strategy aimed at enhancing product purity and net energy efficiency without altering the existing operating conditions. Process simulations were performed to evaluate a modified flowsheet incorporating an additional separator, a second distillation column, and heat-exchanger integration for internal heat recovery. The results show that the modified configuration significantly improves separation performance, raising cyclohexane purity from 57.98% in the basic design to 93.40%. Energy integration through strategic heat-exchanger placement also reduced net energy demand from 910,655,219 kJ/h to 37,151,954 kJ/h, demonstrating substantial thermal-efficiency gains. These findings confirm that equipment-level modifications particularly enhanced separation structures and internal heat-recovery mechanisms can effectively intensify cyclohexane production processes, leading to higher product quality and improved energy sustainability. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).